Unconditional cash transfers and maternal substance use: findings from a randomized control trial of low-income mothers with infants in the U.S. - Paul Y. Yoo; Greg J. Duncan; Katherine Magnuson; Nathan A. Fox; Hirokazu Yoshikawa; Sarah Halpern-Meekin; Kimberly G. Noble (BMC, 2022)
Abstract Background Policy debates over anti-poverty programs are often marked by pernicious stereotypes suggesting that direct cash transfers to people residing in poverty encourage health-risking behaviors such as smoking, drinking, and other substance use. Causal evidence on this issue is limited in the U.S. Given the prominent role of child allowances and other forms of cash assistance in the 2021 American Rescue Plan and proposed Build Back Better legislation, evidence on the extent to which a monthly unconditional cash gift changes substance use patterns among low-income mothers with infants warrants attention, particularly in the context of economic supports that can help improve early environments of children. Method We employ a multi-site, parallel-group, randomized control trial in which 1,000 low-income mothers in the U.S. with newborns were recruited from hospitals shortly after the infant's birth and randomly assigned to receive either a substantial ($333) or a nominal ($20) monthly cash gift during the early years of the infant's life. We estimate the effect of the unconditional cash transfer on self-report measures of maternal substance use (i.e., alcohol, cigarette, or opioid use) and household expenditures on alcohol and cigarettes after one year of cash gifts. Results The cash gift difference of $313 per month had small and statistically nonsignificant impacts on group differences in maternal reports of substance use and household expenditures on alcohol or cigarettes. Effect sizes ranged between − 0.067 standard deviations and + 0.072 standard deviations. The estimated share of the $313 group difference spent on alcohol and tobacco was less than 1%. Conclusions Our randomized control trial of monthly cash gifts to mothers with newborn infants finds that a cash gift difference of $313 per month did not significantly change maternal use of alcohol, cigarettes, or opioids or household expenditures on alcohol or cigarettes. Although the structure of our cash gifts differs somewhat from that of a government-provided child allowance, our null effect findings suggest that unconditional cash transfers aimed at families living in poverty are unlikely to induce large changes in substance use and expenditures by recipients. Trial Registration Registered on Clinical Trials.gov NCT03593356 in July of 2018.